Danza, il rituale dell’inconscio - Capodivacca, Silvia (Scenari, 2021)
“What is dance?” is the main question which is posed at the very beginning of the essay. Many elements, among which the absence of verbal aspects and the importance that is hence accorded to the concept of body (with references to Nietzsche, Deleuze, and Artaud) are the most philosophical, are thus analyzed in order to define this peculiar activity. Nonetheless, the contribution tries to answer the former question by focusing mainly on the topic of the tight relation between dance and the unconscious, of which dance is seen as an explicit, and intentional expression. If dance and unconscious go together, though, it can be further legitimately asked in which way these two ingredients are connected and intermingled: can dance be interpreted a symptom of an unconscious disease or, on the contrary, does it draw the path through which the sufferer can overcome his/her anguishes? After discussing the possibility of these alternatives, the last section of the contribution aims to find a third interpretation of dance, that is then conceived as what leads to the social recognition of the unconscious, which, when its desires and claims are relegated to the sphere of the individual repression or sublimation, suffers and makes the subject get sick. Dance is therefore understood as a plea made by the unconscious that is striving against its interdiction from the social universe.